Experimental study of reinforced concrete columns with embedded pipe - Najafabadi, Sayed Hossein Mousavian (2010)
An experimental study was carried out to investigate the effect of positioning rain water down pipes inside reinforced concrete short braced columns in buildings. Thirty three columns in eleven sets, having various sizes and reinforcements were constructed and tested. The PVC or steel pipes were positioned at the centre of cross-section of each of them. The installation of the strain gauges on the models was carried out before the testing of the models. As an alternative solution, PVC drain pipes were replaced by steel pipes in reinforced concrete columns. The ultimate strength of the columns obtained from the present investigation is compared with the design strengths recommended by the British code of practice (BS 8110) and the American code of practice (ACI). The columns showed significant reduction in their load carrying capacities and the safety factors obtained were much less than the nominal value usually recommended by various codes of practice. Also the study showed that by using steel pipes instead of PVC drain pipes, the load carrying capacity of the columns can be enhanced near 10 percent.